Students with disabilities at spanish universities: date and analysis of the access to higher education - Solera Hernández, Eva; Gutiérrez Gómez-Calcerrada, Sonia; Gonzalez García, Juan Manuel (Inted2015: 9TH international technology, education and development conference, 2020)
Introduction. Spanish laws determine Public Administration must guarantee the access to higher education to students with disabilities by providing equal opportunities and support (Real Decreto Legislativo 1/2013). Nevertheless, in 2007 only 4% of people with disabilities started to study at university (Libro Blanco sobre Universidad y Discapacidad, 2007), and, in 2012, only 14.7% of people with disabilities had got a degree (31.7% among people without disabilities) (Spanish National Statistics Institute, Instituto Nacional de Estadistica, INE, 2012). Objectives. This work outlines two goals. First, to analyze data of access to higher education by type of disability. Second, to find out the causes that create inequality in the access to higher education. This paper mainly focuses on differences in inclusive education between virtual universities and on-site education. Methodology and data. We analyze the "Social Integration and Health 2012 Survey" (INE, 2012) and the reports "University and Disability" (Universidad y Discapacidad, 2014) from "Fundacion Universidad" (University Foundation) and the "Comite Espanol de Representantes de Personas con Discapacidad" (Spanish Committee of Representatives of Persons with Disabilities). We use a mixed design methodological approach: documentary research, focus groups and interviews, and binary logistic regressions. Conclusions. Before going to college, people with disabilities consider attitudinal variables such as the most remarkable barriers to access to higher education. Once they are studying, lack of architectural accessibility is the most relevant barrier.
Keywords: disabilities; university; e-learning; accessibility; WOS(2)